Управление рисками в высокотехнологичных проектах: состояние и подходы управления - Годлевский, М.Д.; Поляков, А.А. (Інститут програмних систем НАН України, 2006)
Анализируется актуальное состояние в области разработки программных проектов и главных факторов в процессах управления
разработкой программных проектов. Одной с проблем является низкий уровень зрелости процессов управления разработкой,
наименьшую зрелость имеют процессы управления рисками. Далее высветляются существующие подходы к управлению рисками и
рассматриваются на примере применения одного из методов управления, который базируется на аппарате имитационного
моделирования. The paper shortly describes and explains current situation of information systems industry and provides overview of the actual problems in
project management process of information systems development. The one of the main problems is low maturity level of management
process in software development and in this cause risk management is one of the key parts of management process that give approach to
complete projects in time with expected results. The paper is research typical approaches in risk management and take into software projects
specific. Also it make an introduction in risk management based on simulation modeling method and shows how its works in real.